2018
DOI: 10.1021/acs.chemrev.8b00201
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting Metalloenzymes for Therapeutic Intervention

Abstract: Metalloenzymes are central to a wide range of essential biological activities, including nucleic acid modification, protein degradation, and many others. The role of metalloenzymes in these processes also makes them central for the progression of many diseases and, as such, makes metalloenzymes attractive targets for therapeutic intervention. Increasing awareness of the role metalloenzymes play in disease and their importance as a class of targets has amplified interest in the development of new strategies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
231
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 218 publications
(246 citation statements)
references
References 1,217 publications
(2,725 reference statements)
0
231
0
1
Order By: Relevance
“…Importantly, from the perspective of structure–property relationship, given that single‐atom catalysts (SACs) with M–N–C structure (M refers to Fe, Mn, Co, etc.) possess similar M–N x sites with natural metalloenzymes, it is expected that this type of SACs can serve as single‐atom nanozymes to mimic the catalytic activity of natural enzymes, such as peroxidase, for the efficient catalytic treatment of bacterial infection. Very recently, Liu and co‐workers first demonstrated that MOF‐derived mesoporous carbon nanospheres containing zinc‐centered porphyrin‐like structure (PMCS) could serve as a single‐atom nanozyme with peroxidase‐like activity, which could inhibit up to 99.87% Pseudomonas aeruginosa and resultantly promote wound healing ( Figure ) 32a.…”
Section: Nanocatalytic Medicine For Nontumoral Therapiesmentioning
confidence: 99%
“…Importantly, from the perspective of structure–property relationship, given that single‐atom catalysts (SACs) with M–N–C structure (M refers to Fe, Mn, Co, etc.) possess similar M–N x sites with natural metalloenzymes, it is expected that this type of SACs can serve as single‐atom nanozymes to mimic the catalytic activity of natural enzymes, such as peroxidase, for the efficient catalytic treatment of bacterial infection. Very recently, Liu and co‐workers first demonstrated that MOF‐derived mesoporous carbon nanospheres containing zinc‐centered porphyrin‐like structure (PMCS) could serve as a single‐atom nanozyme with peroxidase‐like activity, which could inhibit up to 99.87% Pseudomonas aeruginosa and resultantly promote wound healing ( Figure ) 32a.…”
Section: Nanocatalytic Medicine For Nontumoral Therapiesmentioning
confidence: 99%
“…In metalloenzyme inhibition, the carboxylic acid motif routinely participates in metal coordination,a ss een in inhibitors for neutral endopeptidase (NEP), class II fructose-1,6-bisphosphate aldolase (FBP-aldolase), angiotensin-converting enzyme (ACE), and many others. [40] Despite the efficacy of this functional group, its usefulness can be limited in drug development due to poor cell permeability, metabolic instability,a nd off-target effects. [37,39] In an attempt to overcome such liabilities,c hemists turn to the use of prodrugs or isosteric replacement.…”
Section: Introductionmentioning
confidence: 99%
“…Ap rominente xample includes substituting the carboxylic acid functional group with carboxylic acid isosteres. [40] Despite the efficacy of this functional group, its usefulness can be limited in drug development due to poor cell permeability, metabolic instability,a nd off-target effects. [37][38][39] The ionizable nature of the carboxylic acid under physiological conditions (pH 7.4) makes it au seful handle for generating strong inhibitor-target interactions (i.e., electrostatic and hydrogen bonds).…”
mentioning
confidence: 99%
“…The selected targets were: the polymerase acidic Nterminal (PA N ) endonuclease domain from the H1N1 inuenza A virus (antiviral target), New Delhi metallo-b-lactamase-1 (NDM-1; antibacterial target), and the N-terminal domain of heat shock protein 90-a (Hsp90; anticancer target). 47,48 The role of these enzymes in their respective diseases and inhibitor development for each are presented elsewhere. [47][48][49] Briey, PA N endonuclease is one of three proteins in the RNAdependent RNA polymerase complex of the inuenza A virus, along with the polymerase basic protein 1 (PB1) and the polymerase basic protein 2 (PB2).…”
Section: Metallofragment Library Evaluation and Screeningmentioning
confidence: 99%
“…47,48 The role of these enzymes in their respective diseases and inhibitor development for each are presented elsewhere. [47][48][49] Briey, PA N endonuclease is one of three proteins in the RNAdependent RNA polymerase complex of the inuenza A virus, along with the polymerase basic protein 1 (PB1) and the polymerase basic protein 2 (PB2). 50 PA N endonuclease contains a dinuclear metal active site, with two Mn 2+ or Mg 2+ cations that promote endonuclease activity.…”
Section: Metallofragment Library Evaluation and Screeningmentioning
confidence: 99%